The use and analysis of African languages in the former Model C schools : A case study - Sithole, Kateko Lucy (University of Limpopo (Turfloop Campus), 2013)
The study discovered that above mentioned situation has hardly changed English in the in the school under review is fill medium of instruction of the majority of learners,power of Afrikaans. A major recommendation of the study is that African languages should be introduced as medium of infraction for African language speakers in all former model school
Thesis ( M.A. (African languages)) --University of Limpopo, 2013
Keywords: African languages; Model C schools; 306.4490968; Language policy -- South Africa; Education -- Curricula; Education, Urban -- South Africa